2017
DOI: 10.14411/fp.2017.030
|View full text |Cite
|
Sign up to set email alerts
|

Myxobolus pseudowulii sp. n. (Myxozoa: Myxosporea), a new skin parasite of yellow catfish Tachysurus fulvidraco (Richardson) and redescription of Myxobolus voremkhai (Akhmerov, 1960)

Abstract: Two species of Myxobolus Bütschli, 1882 were found in yellow catfish Tachysurus fulvidraco (Richardson). A species of Myxobolus infecting the gills was morphologically identified as Myxobolus voremkhai (Akhmerov, 1960) and it was characterised here with additional morphological and molecular data. The other species of Myxobolus infecting the host's skin did not conform to any known myxosporean species. It is characterised by the presence of round, black or milky white plasmodia with black spots. Myxospores are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
3
9
0
2
Order By: Relevance
“…Studies of another speciose myxozoan group, the Myxobolidae, have shown that closely related myxobolids have closely related vertebrate host species [40–43]. While we recovered this pattern among ceratomyxids, with many clades of Ceratomyxa sharing common host orders (), we also found that closely related ceratomyxids infect different host orders, and some host orders are shared by parasites from multiple clades.…”
Section: Discussionsupporting
confidence: 47%
“…Studies of another speciose myxozoan group, the Myxobolidae, have shown that closely related myxobolids have closely related vertebrate host species [40–43]. While we recovered this pattern among ceratomyxids, with many clades of Ceratomyxa sharing common host orders (), we also found that closely related ceratomyxids infect different host orders, and some host orders are shared by parasites from multiple clades.…”
Section: Discussionsupporting
confidence: 47%
“…Moreover, this myxozoan sequence was detected only once in A. brama (Baska 1987, Forró andEszterbauer 2016) and once in Scardinius erythrophthalmus. Most of other M. pseudodispar related clades studied in the present work have also a narrow host spectrum similarly as many other species of Myxobolus, e.g., M. bejeranoi Lövy, Smirnov, Brekhman, Ofek et Lotan, 2018 from hybrid tilapia of Oreochromis aureus (Steindachner) male × Oreochromis niloticus (Linnaeus) female, or M. pseudowulii Zhang, Zhai, Liu et Gu, 2017 from the yellow catfish Pylodictis olivaris (Rafinesque) (Zhang et al 2017, Lövy et al 2018. The Abramis clade is the exception of the narrow host spectrum with four hosts (Abramis brama, Blicca bjoerkna, Perca fluviatilis and Sabanejewia bulgarica) detected to be infected by this myxobolid.…”
Section: Discussionmentioning
confidence: 52%
“…are rather host specific parasites infecting mostly a single species ( Akhmerov, 1955 , 1960 ; Molnár, 1982 ; Shin et al, 2014 ). Moreover, recent studies prove that most species can be characterized by strict tissue and organ specificity ( Akhmerov, 1955 ; Molnár and Eszterbauer, 2015 ; Liu et al, 2016 ; Zhang et al, 2017 ). The synopsis on Thelohanellus by Zhang et al (2013) focused to designate only the host and organ from where the Thelohanellus species were first described.…”
Section: Introductionmentioning
confidence: 99%